(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the learning outcomes of medical students at Dai Nam University in 2024. Research subjects and methods: Cross-sectional descriptive study using Google form on 274 medical students at Dai Nam University in 2024. Results: The average first semester final score of students in the study was 6.9 ± 1.1 (5 – 9.2) points. Most students have academic results ranked average or below (63.1%). The rate ranked excellent or better in the previous semester was 11.3%. More than one-third of the students in the study had to retake at least one course (36.1%) in the previous semester, and 22.3% of students had debt for at least one subject that needed to be retaken. On average, a student had to retake 0.5 ± 0.8 subjects in the previous semester (0 – 4 subjects) and still owed 0.4 ± 1.1 subjects (0 – 9 subjects). Female students have a higher academic rating of good or better than male students. Academic results with excellent grades and above also gradually increased in first-year to fourth-year students. Conclusion: Academic results were relatively high based on final academic ranking, but the rate of retakes in the previous semester and course debt up to the time of the study were also significant in the study group. Female students and older grades students had better academic results than other groups.